Endodontic reintervention of the maxillary third molar with type ii vertucci root canal classification: Case report - Indriyatmi, Rosida; Hikmah, Noor; Natsir, Nurhayaty; Nugroho, Juni J.; Trilaksana, Aries C.; Dwiandhany, Wahyuni S. (Journal of Case Reports in Dental Medicine, 2023)
Objective: The aim of this case report is to describe endodontic reintervention of a maxillary third molar with Vertucci type II root canal classification.Methods: Root canal treatment was done one year ago. Intraoral examination showed composite fillings, a thermal test (-), percussion (+), and palpation (-). A periapical radiograph shows non-hermetic obturation. Endodontic reintervention was performed by removing gutta- percha using H-File (Dentsply, Switzerland) and xylol solution, followed by determination of working length and confirmation with an apex locator (Propex Pixi, Dentsply, Switzerland). Results: The anatomic variation of the root canal is a complicating factor that results in the failure of the treatment performed. Vertucci type II root canal classification is one of the anatomic variations that complicate instrumentation, which causes treatment failure and requires endodontic re-intervention.Conclusion: Endodontic reinvention of the maxillary third molar with Vertucci type II root canal classification can provide optimal results with the right treatment plan and adequate restoration.